Evaluation of the Inflammatory Cytokines and IL-10 Network in Individuals Co-infected With Human T-Cell Lymphotropic Virus and Hepatitis C Virus (HTLV/HCV) - Pereira, Felicidade Mota; Ramos, Pablo Ivan Pereira; Lirio, Monique; Mercês Atta, Ajax; Silva de Oliveira, Isabela; Nascimento, Fabio Carneiro Vosqui; Silva, Marcelo Costa; Galvão-Castro, Bernardo; Rios Grassi, Maria Fernanda (Frontiers in Microbiology, 2021)
Background: Coinfection between the human T-cell lymphotropic virus (HTLV) and the hepatitis C virus (HCV) can modify the natural history of HCV infection. The aim of this study was to describe the inflammatory cytokines and IL-10 network in patients coinfected with HTLV and HCV viruses in Bahia, Brazil. Methods: Samples from 31 HTLV/HCV coinfected individuals and 27 HCV monoinfected individuals were evaluated. IFN-γ, TNF-α, IL-10, IL-8 and IL-1 cytokines were quantified by ELISA. Clinical, laboratory data were obtained from patient records. Serum levels of the cytokines were log10-transformed and data mining was performed using Z-score statistics and correlation analysis. Results: Coinfected individuals presented a tendency towards higher production of INF-γ compared to the HCV monoinfected group. Regarding cytokine pairs, there was a positive correlation (P-value <0.05) between IL-1 and IL-8 in the HTLV/HCV coinfected group and uninfected controls, and two correlations in the HCV mono-infected group IL-8 - IL10 and IL- INF-γ - IL-10 pairs. There was no significant difference between the groups for the other parameters analyzed. Conclusion: The results presented herein indicated that HTLV/HCV coinfection was associated with a trend in IFN- production while HCV-infected individuals presented a positive correlation with both inflammatory cytokines (IL-8 and IFN-) and the regulatory cytokine IL-10.